Understanding Responsibility Accounting at KUD BATU - Rahmawati, Annisa; Kamayanti, Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This thesis aims to understand and to gain understanding of the responsibility accounting and itspractice at the KUD BATU of Batu city. Qualitative methods are employed through in-depthinterviews to three actors of KUD BATU who have served as the core committee and have beenworking in KUD BATU for more than 36 years. The results of the interviews are used in this studyin order to obtain valid and accurate data. This study examines issues related to theinterpretation of responsibility accounting and its implementation in KUD BATU. Since 2005,KUD BATU had been implementing responsibility accounting. The organizational structure ofKUD BATU was already satisfying. The effective budgeting and cooperation had alreadyseparated controllable and uncontrollable costs, but the accountability reports writing did notinvolve lower management. The perpetrators of KUD BATU interpreted that responsibilityaccounting was essential for KUD BATU because it provided accurate transaction / financialstatements. Since the implementation of responsibility accounting systems, the financial system ofKUD BATU had been more orderly, structured, and consistent. More effective budgeting andaccountability reports were created to provide income that could increase the make milkproduction of KUD BATU.Key Word: Responsibility accounting, organization structure, planning, implementation,reporting.